2015
DOI: 10.1371/journal.pone.0133924
|View full text |Cite
|
Sign up to set email alerts
|

Lower Pre-Treatment T Cell Activation in Early- and Late-Onset Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome

Abstract: BackgroundTuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is an inflammatory complication in HIV-TB co-infected patients receiving antiretroviral therapy (ART). The role of disturbed T cell reconstitution in TB-IRIS is not well understood. We investigated T cell activation and maturation profiles in patients who developed TB-IRIS at different intervals during ART.MethodsTwenty-two HIV-TB patients who developed early-onset TB-IRIS and 10 who developed late-onset TB-IRIS were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
(64 reference statements)
2
11
1
1
Order By: Relevance
“…These findings are similar to several other investigations [14,16] and are generally consistent with our previous report documenting reduced pre-ART systemic inflammation in those who later developed TB-IRIS [15]. Furthermore, we found no enrichment in late differentiation stage CD4 + T-cells in TB-IRIS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are similar to several other investigations [14,16] and are generally consistent with our previous report documenting reduced pre-ART systemic inflammation in those who later developed TB-IRIS [15]. Furthermore, we found no enrichment in late differentiation stage CD4 + T-cells in TB-IRIS.…”
Section: Discussionsupporting
confidence: 94%
“…Immunologically, higher pre-ART levels of immune activation and rapid increases in tuberculosis-specific interferon gamma (IFN-γ)-producing cells after ART initiation in HIV-infected adults have been associated with development of TB-IRIS [7,[9][10][11][12]. However, in several recent studies, levels of pre-ART immune activation were actually lower in TB-IRIS patients vs controls [13][14][15], and multiple reports have indicated that patients without TB-IRIS may also have robust increases in levels of pathogen-specific immune responses on ART [16,17]. Existing data are therefore inconclusive about whether higher levels of pre-ART immune activation predispose to TB-IRIS and whether tuberculosis-specific T-cells are involved in TB-IRIS pathogenesis.…”
mentioning
confidence: 99%
“…Moreover, clinical risk factors already known to be associated with IRIS pathogenesis are (a) low baseline CD4 + T-cell count (< 50-100 cells per mm 3 ) combined with a short time interval between the beginning of TB treatment and cART [38][39][40][41][42] and (b) dissemination of TB to extrapulmonary sites, possibly reflecting a high bacterial load [43,44]. Nevertheless, despite the few biomarker descriptions associated with IRIS, there is still no one capable of predicting IRIS development currently being used in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, after ART treatment initiation, the CD4 T cell memory was skewed towards effector-memory phenotype [32]. In another study, it was postulated that low CD8+ T cell activation (HLA-DR+/CD38+) could be a predisposing factor of both early and late onset TB-IRIS events and that late but not early onset IRIS showed a shift from memory to effector CD8+ and CD4+ T cells after ART initiation [33]. Wilkinson KA et al, studied also the effector function of TB-specific CD4 T cells and demonstrated an increase in IFN-gamma response as well as in perforin 1 and granzyme B expression in heat-killed H37Rv stimulated human PBMCs from paradoxical TB-IRIS patients compared to HIV-TB co-infected non-IRIS patients [34] further highlighting the effector function of TB-specific cells.…”
Section: Introductionmentioning
confidence: 99%